Correlates of psychological outcomes among family members of people with diabetes in the second Diabetes Attitudes, Wishes and Needs (DAWN2™) study. Issue 9 (26th May 2016) - Kovacs Burns, K.; Holt, R. I. G.; Nicolucci, A.; Lucisano, G.; Skovlund, S. E.; Comaschi, M.; Vallis, M.; Peyrot, M.
Abstract: Aims: To conduct a second Diabetes Attitudes, Wishes and Needs (DAWN2 ™ ) study, examining the experiences of family members caring for adults with diabetes in order to identify correlates of family member psychological outcomes (generic psychological well‐being, perceived quality of life, and diabetes‐related burden, impact and distress). Methods: A total of 2057 family members living with a person with diabetes and involved in their care participated in an online, telephone or in‐person survey. Samples of 120 respondents were recruited in each of 17 countries. Significant ( P < 0.05) correlates of psychological outcomes were identified by multi‐level multiple regression. Results: Outcomes were worse for family members not working because of diabetes or those who had other competing obligations. Outcomes were worse if the person with diabetes was not a partner or parent, used injected diabetes medication, or had more frequent hypoglycaemia. Outcomes were worse for family members who believed that diabetes was more severe, were more involved in diabetes care, had more conflict over diabetes care or were frustrated about not knowing how to help the person with diabetes. Outcomes were better for those who had greater support from others and felt they found good ways to help the person with diabetes. There were significant differences in outcomes among countries before and after adjustment for individual characteristics, and correlates of outcomes varied by country. Conclusions: Several modifiable risk and protective factors for family member psychological outcomes were identified in this study. Diabetes education and social support were associated with improved outcomes, especially if they were helpful in supporting people with diabetes. What's new?: DAWN2, conducted in 17 countries across four continents, is the first study to identify key sociodemographic, treatment‐related, psychosocial and behavioural factors associated with psychological outcomes for adult family members of adults with diabetes. Older age, not working because of diabetes, lower education or lower levels of education, use of injectable medicine by the person with diabetes, worry about hypoglycaemia, high perceived severity of diabetes and experience of discrimination on the part of the person with diabetes were associated with worse psychological outcomes among adult family members of people with diabetes. Family arguments about diabetes management, frustration with not knowing how best to help, and greater responsibility for diabetes management were associated with worse psychological outcomes for family members of people with diabetes. Knowing good ways to support, providing more support for diabetes and having access to more people to talk to about diabetes challenges were associated with better psychological outcomes. The study extends earlier evidence from the DAWN2 study highlighting the psychosocial impact of diabetes on family members and identifies globally important factors for psychological well‐being of family members of adults with diabetes which need to be considered in future efforts to improve diabetes care.